The EFFECT OF LONG-TERM DEBT, SHORT-TERM DEBT AND TAX EXPENSES ON THE PROFITABILITY OF COMPANIES IN THE JAKARTA ISLAMIC INDEX (JII): PENGARUH HUTANG JANGKA PANJANG, HUTANG JANGKA PENDEK DAN BEBAN PAJAK TERHADAP PROFITABILITAS PERUSAHAAN DI JAKARTA ISLAMIC INDEX (JII) - Wina Mairlina; A.A Miftah; Ahmad Syahrizal (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine how the effect of long-term debt, short-term debt and tax burden on profitability in the Jakarta Islamic Index (JII). This research use quantitative methods. The data analysis method is using Multiple Linear Regression. The sample used in this study is financial statements of companies registered with JII for the period 2016 to 2020. This study resulted in long-term debt having negative and significant effect on profitability, short-term debt having a significant and positive effect on profitability and tax expense had no effect on profitability.